Collaboration and Community Participation in Tourism Development - Herlina Sakawati; Haedar Akib; Sulmiah Sulmiah; Widyawati Widyawati (Jurnal Office, 2022)
This study discusses collaboration and community participation in tourism development in Malino Village, Gowa Regency. Malino Village has the best tourism destinations in South Sulawesi, and its management involves several parties. However, the involvement of these parties has not been well established in the cooperative relationship. Community involvement in tourism management is also considered to be still lacking. To realize tourism development in Malino Village requires collaboration between every party involved and community involvement. The data that is the study material in this study was obtained from the results of interviews, observations, and literature studies. Existing data were analyzed using Interactive Model Analysis. From the results of the analysis, it is known that the Gowa Regency Government does not have a collaborative foundation in tourism development. The cooperative relationship that exists is not based on the goal of overcoming tourism problems in Malino Village. Cooperation is carried out based on the interests of each. Community support in the development of tourism is realized by managing and maintaining the facilities and infrastructure to support the implementation of tourism prepared by the government. In order for the development of tourism in Malino village to be implemented properly, the Gowa Regency government should carry out collaboration in the form of business clusters.